Islamic Solidarity and Ta'awun: A Case Study of Community Responses to Rohingya Refugees in Sabang, Aceh - Suarni, Suarni; Nufiar, Nufiar; Miskahuddin, Miskahuddin; Aulia, Ade; Rusdi, Mikdar; Zakia, Shabira (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2024)
The principle of ta'awun (mutual assistance) is a fundamental Islamic value that promotes solidarity and shared responsibility. Its practical application in contemporary, culturally diverse societies often encounters significant challenges. This study investigates how the residents of Ie Meulee Village, Sukajaya Subdistrict, Sabang City, practiced ta'awun in responding to Rohingya refugees stranded in the area during December 2023. Employing a qualitative methodology, the study collected data through observations, interviews with 14 informants—including village officials, religious leaders, community members, and refugees—and document analysis. The findings reveal varied interpretations and implementations of ta'awun, shaped by factors such as religious education, the social environment, and economic constraints. While residents with strong religious knowledge exhibited proactive assistance, others provided help spontaneously or hesitated due to existing prejudices. This study underscores the importance of inclusive religious education, community-based social programs, and local policies to foster cross-cultural solidarity, ensuring the sustainable application of ta'awun values in multiethnic societies.